2018
DOI: 10.3144/expresspolymlett.2018.42
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic study of Tensylon®–based panels

Abstract: Ballistic protection is a matter of interest requested by civilian as well as military needs. The last decade has witnessed an increase in the use of light weight and efficient armour systems. These panels may be used for body protection as well as light vehicle protection against small calibres or to enhance the protection level of heavier vehicles with decreasing or maintaining their weight penalty. Ultra high molecular weight polyethylene is a material of interest for light weight armour applications. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The influence of the interfacial stiffness parameter has been studied and it is observed that its best value is of 2.5.10 +11 N. Larger values yielded to underestimate the bulging of the free surface when it is spalled. The numerical simulation of the delamination showed a multi delamination, suspected since observed in larger samples impacted by real bullets in [15] but not evidenced in thinner samples subjected to laser induced shock waves due to the difficulty of obtaining a clear cut and polishing of the recovered samples. This is an issue that could be extensively prospected by the future use of a high resolution microtomograph.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The influence of the interfacial stiffness parameter has been studied and it is observed that its best value is of 2.5.10 +11 N. Larger values yielded to underestimate the bulging of the free surface when it is spalled. The numerical simulation of the delamination showed a multi delamination, suspected since observed in larger samples impacted by real bullets in [15] but not evidenced in thinner samples subjected to laser induced shock waves due to the difficulty of obtaining a clear cut and polishing of the recovered samples. This is an issue that could be extensively prospected by the future use of a high resolution microtomograph.…”
Section: Discussionmentioning
confidence: 92%
“…They suggested a Young Modulus of 3000 MPa, Poisson ratio of 0.47, Yield stress of 60 MPa and Tangential modulus of 500 MPa. In [15], a full UHMWPE plate of 500Ã500 mm was impacted with 7.62Ã39 mm FMJ with lead core bullet at 700 m/s. Micro and macroscopic observations are given and among dissipative mechanisms identified, multi-delamination is observed.…”
Section: Samples Descriptionmentioning
confidence: 99%
“…Indeed, in the regime of interest thermal effects are generally considered negligible [32], as later confirmed by results. Parallel, some experiments would confirm that this assumption is reasonable up to 700-800m∕s, when melting may start to occur for the thermoset resin or PE fibers [33].…”
Section: Analytical Impact Modelmentioning
confidence: 82%